Prevalence of cleft lip and palate in a hospital-based population in the Sudan - A. M. SULEIMAN, S. T. HAMZAH, M. A. ABUSALAB, & K. T. SAMAAN (Paediatric Dentistry, 2005)
Cleft lip and palate may present a very varied clinical picture, depending, at least partly, on the severity of the condition. The cause is known to be multifactorial in nature, and to include both environmental and genetic factors [1].